The impact of branchless banking to business performance: case study at BSN - Muhammad Khairul Haziq, Muhd Fuzi (2013)
The aim of this research is to study the impact of branchless banking to business performance. Branchless banking has great potential to extend the distribution of financial services to poor people who are not reached by traditional bank branch networks. It lowers the cost of delivery, including costs both banks of building and maintaining a delivery channel and to customers of accessing services. Branchless banking helps Bank Simpanan Nasional to improve their business performance since the introduction. This study is conducted by using qualitative method which is interview.